Teaching experimental political science - Bennion, Elizabeth A.; Edward Elgar Publishing (Northampton : Edward Elgar Publishing, 2024)
"This insightful book delivers a wealth of innovative ideas, models, examples, and advice for teaching experimental political science in the classroom and beyond, emphasising that teaching experimental research is necessary to prepare students to succeed as researchers, practitioners, active citizens and civic leaders. It illustrates how teaching experimental methods sparks students' curiosity by allowing them to ask and answer questions about the world they live in. With a core focus on successfully engaging a diverse range of students at all levels, this book includes a variety of approaches from contributing authors who are leading scholars in their field. Chapters provide both new and experienced teachers with concrete guidance on how to: facilitate student-designed survey experiments, use workbooks and templates to overcome mathematical and writing anxiety; use mock Institutional Review Board (IRB) reviews to teach students about the ethics of experimental research; follow an apprenticeship model to teach students to carry out their own lab experiments; and train students to go out into the field. Proposed models of teaching are supported throughout by the latest empirical research on the science of learning. Teaching Experimental Political Science will be a key resource for faculty and staff working across a variety of educational contexts including political science, international relations, international politics, domestic politics, public administration and public policy"--
Contents: Introduction: Innovative approaches to teaching experimental methods in the political science classroom / Elizabeth A. Bennion -- 1. Experiments for all! Introducing freshmen to social science research using innovative experiments / Debra Leiter and Beth Miller Vonnahme -- 2. Included and set up to succeed: An evidence-based approach to teaching experiments in the diverse classroom / Elaine K. Denny and Reagan Bijou -- 3. Engaging students as researchers: The value of an inquiry-based one-semester survey experiment / Jeffrey L. Bernstein -- 4. Using class-designed survey experiments to teach data collection, analysis, and reporting protocols / Jennifer Bachner -- 5. Using templates to make survey experiments accessible to math-anxious students / Eric Loepp -- 6. Nurturing problem-solvers: Using workbooks to teach experiments in international development / Lindsay R. Dolan -- 7. Incorporating experimental methods training into your political science courses: A practical, topic-informed approach / Angie Bos and Bas van Doorn -- 8. From concept to implementation: Engaging student researchers in get-out-the-vote field experiments / Melissa R. Michelson and Mara Ostfeld -- 9. Train the trainer: A field experiment workshop for graduate students and faculty / Elizabeth I. Dorssom -- 10. Teaching lab experiments using an apprenticeship model / Rose McDermott -- 11. Using mock institutional review boards to teach the ethics of experimental research / Christopher B. Mann -- 12. When things go wrong in the lab: Teaching new experimenters to anticipate and adapt to the unexpected / Jonathan Rogers -- 13. Creating an experimental lab on your campus / Kim Fridkin, Manuel Gutierrez, Trudy Horsting, and Alexandra M. Williams -- Index.
Includes bibliographical references and index.
Keywords: elektronické knihy; electronic books; Education -- Experimental methods; Political science -- Study and teaching